Molecular genetics reveal that silvatic Rhodnius prolixus do colonise rural houses. - Sinead Fitzpatrick; Maria Dora Feliciangeli; Maria J Sanchez-Martin; Fernando A Monteiro; Michael A Miles (Public Library of Science (PLoS), 2008)
Rhodnius prolixus is the main vector of Chagas disease in Venezuela. Here, domestic infestations of poor quality rural housing have persisted despite four decades of vector control. This is in contrast to the Southern Cone region of South America, where the main vector, Triatoma infestans, has been eliminated over large areas. The repeated colonisation of houses by silvatic populations of R. prolixus potentially explains the control difficulties. However, controversy surrounds the existence of silvatic R. prolixus: it has been suggested that all silvatic populations are in fact Rhodnius robustus, a related species of minor epidemiological importance. Here we investigate, by direct sequencing (mtcytb, D2) and by microsatellite analysis, 1) the identity of silvatic Rhodnius and 2) whether silvatic populations of Rhodnius are isolated from domestic populations.Direct sequencing confirmed the presence of R. prolixus in palms and that silvatic bugs can colonise houses, with house and palm specimens sharing seven cytb haplotypes. Additionally, mitochondrial introgression was detected between R. robustus and R. prolixus, indicating a previous hybridisation event. The use of ten polymorphic microsatellite loci revealed a lack of genetic structure between silvatic and domestic ecotopes (non-significant F(ST) values), which is indicative of unrestricted gene flow.Our analyses demonstrate that silvatic R. prolixus presents an unquestionable threat to the control of Chagas disease in Venezuela. The design of improved control strategies is essential for successful long term control and could include modified spraying and surveillance practices, together with housing improvements.